Serum procalcitonin measurement for detection of bacterial infection vs disease flare in SLE patients / Nurul Faatima Ahmad Zabidi - Nurul Faatima, Ahmad Zabidi (2017)
Background: Infection is one of the leading cause of morbidity and mortality in systemic lupus erythematosus (SLE). It is important to identify and differentiate bacterial infections and disease flare in SLE patient at an early stage because the treatment modalities for each condition differs. This study aims to evaluate the possible role of procalcitonin for detection of bacterial infections in SLE patients presenting with signs and symptoms of infection and/or disease flare. Method: This is a cross sectional case control study involving 72 female SLE patients. 36 hospitalised SLE patients with symptoms suggestive of infections and/or disease flares were recruited with the remaining 36 stable SLE patients as controls over a 10 month interval. Patients were classified into three groups; bacterial infection, nonbacterial infection (disease flare and viral infection) and stable. Serum PCT were assessed in all these patients. Results: The disease group (n=36) comprised bacterial infection (n=10) and 26 nonbacterial origin (20 were disease flare and 6 viral infection). PCT value at 0.28ng/ml (80% sensitivity, 100% specificity, 100% PPV and 91 % NPV) was found to be the most appropriate cut off value for detecting bacterial infection among SLE patients presenting with signs and symptoms of infection and/or disease flare. Whilst PCT level of <0.09ng/ml was deemed to be the appropriate cut off point for stable SLE patients without any infection or disease activity. Conclusion: Elevated PCT has a good specificity and positive predictive value and may potentially be utilized in differentiating bacterial infection from disease flare in SLE patients. Key Words: SLE, Bacterial Infections, Procalcitonin, Disease Flares.